Histopathology and proteomics are synergistic for high-grade serous ovarian cancer platinum response prediction - Oz Kilim; Alex Olar; András Biricz; Lilla Madaras; Péter Pollner; Zoltán Szállási; Zsofia Sztupinszki; István Csabai (npj Precision Oncology)
Abstract Patients with High-Grade Serous Ovarian Cancer (HGSOC) exhibit varied responses to treatment, with 20–30% showing de novo resistance to platinum-based chemotherapy. While hematoxylin-eosin (H&E)-stained pathological slides are used for routine diagnosis of cancer type, they may also contain diagnostically useful information about treatment response. Our study demonstrates that combining H&E-stained whole slide images (WSIs) with proteomic signatures using a multimodal deep learning framework significantly improves the prediction of platinum response in both discovery and validation cohorts. This method outperforms the Homologous Recombination Deficiency (HRD) score in predicting platinum response and overall patient survival. Our study suggests that histology and proteomics contain complementary information about biological processes determining response to first line platinum treatment in HGSOC. This integrative approach has the potential to improve personalized treatment and provide insights into the therapeutic vulnerabilities of HGSOC.